Crucial Role of the Chaperonin GroES/EL for Heterologous Production of the Soluble Methane Monooxygenase from Methylomonas methanica MC09. (29th April 2022) - Zill, Domenic; Lettau, Elisabeth; Lorent, Christian; Seifert, Franziska; Singh, Praveen K.; Lauterbach, Lars
Abstract: Methane is a widespread energy source and can serve as an attractive C1 building block for a future bioeconomy. The soluble methane monooxygenase (sMMO) is able to break the strong C−H bond of methane and convert it to methanol. The high structural complexity, multiplex cofactors, and unfamiliar folding or maturation procedures of sMMO have hampered the heterologous production and thus biotechnological applications. Here, we demonstrate the heterologous production of active sMMO from the marine Methylomonas methanica MC09 in Escherichia coli by co‐synthesizing the GroES/EL chaperonin. Iron determination, electron paramagnetic resonance spectroscopy, and native gel immunoblots revealed the incorporation of the non‐heme diiron centre and homodimer formation of active sMMO. The production of recombinant sMMO will enable the expansion of the possibilities of detailed studies, allowing for a variety of novel biotechnological applications. Abstract : Methane monooxygenase : The chaperonin GroES/EL enables folding and correct assembly of soluble methane monooxygenase (sMMO) heterologously produced in Escherichia coli . The production of recombinant sMMO will enable a variety of novel biotechnological applications in future.